Exploring the Global Development of Artificial Intelligence in Educational Practices - Merliana, Miranti; Tanzil, Muhammad; Qaylan, Nadzir (Multicultural Islamic Education Review, 2025)
The rapid integration of Artificial Intelligence (AI) into global education systems has transformed learning processes, yet the existing literature remains fragmented, lacking a comprehensive understanding of its global research dynamics . This study aims to determine the mapping of the development and direction of education and technology research in publications indexed by Scopus. This research uses bibliometric analysis techniques to explore all publications indexed in the Scopus database on education and technology from 2014 to 2024. Data analyzed using Excel and R/R-Studio. VOSviewer is used to perform visual analysis of the simultaneous occurrence of keywords and document quotes. The author found 381 publications that matched the function, subject and criteria specified. The results of this research show an annual growth rate of 6.25% with the most publications about technology in 2013. Taiwan is the country that contributes the most publications with affiliation from education technology University Taiwan. Hwang G.J is the most productive writer on the theme of education relevant to technology. The bibliometric analysis carried out was limited to Scopus data. Other national and international databases were not taken into account in this study. This research presents a brief overview of the literature accessible to researchers working in the fields of Education and technology that provides recommendations for future research.